MERANCANG PROSES PEMBELAJARAN PKN YANG MENYENANGKAN DI SMP N 4 PELEPAT ILIR - Sukarno Sukarno (PAKAR Pendidikan, 2016)
PKn Subject is the cultivication concept subject of national awareness, Pancasila, hard working attitude and responsiblity. Most of its material are concept. For giving the materials of learning, teacher have to have their own trick, so that the materials can be planned in easy by student. This research design study process which is fun for student at PKn subject. Interlude technique at learning is designed in order to support learning in the class. As a result, this research can increase the student study report.